Eksistensi Tradisi Masyarakat Samin Kabupaten Bojonegoro di Era Modern - Agus Danugroho (LP4MK STKIP PGRI Lubuklinggau, 2020)
Traditions that run in society contain norms and values that become part of a group of nations and their supporters. The socialization activities were held for the sake of appreciation of the tradition by each of the supporting communities. One element of tradition in a culture is belief in the form of religion and symbols in it. Samin can be said to be a form of community that is still developing in Java, especially in East Java and Central Java. One of them is the Samin community which is still developing until now in the Japanese Hamlet, Margomulyo Village, Margomulyo District, Bojonegoro Regency. This study raised the existence of the tradition of the Samin Bojonegoro community in this modern era. This is expected to add insight to the readers and especially the local Bojonegoro community to respect and preserve the traditions of their ancestors and not forget the local identity of the region. This study uses historical methods that have heuristic stages, source criticism, interpretation and historiography. This is because this research is related to the object to be studied, namely in the form of history and traditions that exist in the community which can only be explained through descriptions. This research is closely related to the process of collecting primary and secondary data. Primary sources are used in the form of documents, literature studies, observations and interviews with traditional leaders, organizers, and communities directly related. In addition, secondary sources are used in the form of previous research and literature. This research resulted in the existence of the tradition of the Samin community in the Bojonegoro region in this modern era. Keywords: Existensi, Tradition, Samin, Bojonegoro.